Designing safety interventions for specific contexts - Pilbeam, Colin; Karanikas, Nektarios; Steinmann, Fabian; Baker, Philip; Khan, Shanchita (Lloyd’s Register Foundation, 2022)
Executive Summary Workplace health and safety (H&S) is a significant global issue; around 500 million people are adversely affected by work-related injuries and illnesses each year, while the number of daily workplace fatalities runs into the thousands. One explanation for these alarming statistics may lie in the way safety interventions are introduced and implemented in different contexts. A ‘safety intervention’ could be any physical artefact, process, procedure, skills, or specialist knowledge that restores, maintains, or strengthens safety (i.e., prevents or mitigates safety risks; influences culture and behaviours; improves health and wellbeing; ensures compliance with legal requirements). Misalignment between interventions and context increases the possibility of failure with adverse consequences. Where interventions ‘fit’ the context safety performance is high. There is a clear requirement to minimise harm and maximise worker well-being in the workplace, a change that can be driven by the implementation of context-appropriate safety interventions. However, the degree to which organisations and occupational H&S researchers, and trainers contemplate contextualisation processes, and the variables that influence these processes, when sourcing, designing and implementing safety interventions is unclear and may account for the lack of success observed for some interventions. In this report we attempt to address this knowledge gap and present the findings of our investigation into whether and how researchers, trainers, and organisations consider contextual factors in safety interventions. The study comprised of three broad strands. Firstly, a comprehensive Rapid Evidence Assessment (REA) reviewed scholarly work published in peer-reviewed journals between 2011 and 2021; from an initial sample of 3,450 studies, 73 studies were included in the final review. Secondly, a screen of nationally and internationally recognised training materials, coupled with 12 semi-structured interviews with experienced trainers, was performed to determine how frequently safety courses considered context. Finally, further interviews with industry stakeholders were performed to identify both successful and unsuccessful interventions and to ascertain if context was a factor in outcomes. We identified that training and education was the most frequently applied intervention, and training providers confirm that they believe appropriate consideration of context would increase the effectiveness of interventions. However, it was also clear that few courses consider the influence of context on the interventions or describe a framework whereby such contextualisation could occur. For example, interventions are often ‘borrowed’ from other organisations and are not adjusted to meet the specific needs of the new environment. This, coupled with the observation of a widespread failure of organisations to review the impact of their safety training in a continuous fashion and update and improve its implementation, suggests that there is a need for organisational level adjustments. We, therefore, suggest that the following five recommendations are developed to improve the training of workplace H&S, and thus its implementation: 1. Organisations should begin considering the context of interventions as much as the intervention itself during implementation. This process can be assisted via the development of the processes detailed below. 2. Organisations, occupational safety and health (OSH) training providers, OSH institutions and agencies, and academia should develop guidelines that indicate key success factors (KSFs) for safety training effectiveness within the organisational context, and how these 3 KSFs can be achieved. These would consider organisational characteristics, trainee demographics and features of the intervention. 3. Organisations, OSH training providers, OSH institutions and agencies, and academia should develop guidelines for designing online safety training materials that consider context. This should consider aesthetics, usability and usefulness drawing on existing knowledge of technology acceptance. 4. Organisations, OSH training providers, OSH institutions and agencies, and academia should develop guidelines to produce immersive, interactive, digital content for contextually relevant safety training materials to meet growing demand. 5. OSH training providers, OSH institutions and agencies and OSH regulators should promote the need to review the benefits of safety training after the event and to review current understanding before re-training. In addition, the field would benefit from further research to better describe methodologies and frameworks that will allow for efficient contextualisation of H&S interventions across a wide range of industries. These have been specified in a further set of 11 recommendations.